Rancangan Sistem Pengukuran Konsentrasi Emisi Gas Karbon Dioksida Berbasis IoT di Berbagai Area Sumber Emisi Udara - Kasnawi Al Hadi; Arif Budianto; Ni Ketut Anggriani (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This study aims to design an IoT (internet of things)-based CO2 concentration measurement system and to identify environmental parameters that affect it. The measurement system was designed using an MG-811 sensor, internet network, and database as a transmitter station. The measurement system was calibrated to identify static measurement characteristics, such as accuracy, selectivity, measurement range-span, and response time. The system was installed in four emission sources: (a) rice fields that were actively burning agricultural waste; (b) landfills, (c) food courts, and (d) areas around the industry. Each area was connected to the receiver station for seven consecutive days. The calibration process shows good selectivity for CO2 gas, with a response of 1500 ppm). The difference in concentration was influenced by wind direction, air humidity, and emission factors. The results of the study concluded that the concentration measurement system can be developed into an IoT-based air quality monitoring system. CO2 concentration was influenced by environmental parameters, such as air humidity, wind direction, and type of emission source.